Seasonal Changes of Extremes in Isolated and Mesoscale Precipitation for the Southeastern United States - Rickenbach, Thomas (My University, 2018)
The association between instantaneous extreme precipitation and mesoscale organization over the southeastern United States is not well known. This study addresses whether isolated precipitation features have a distinct distribution and spatial pattern of extreme rain compared to mesoscale precipitation features, and how these distributions and spatial patterns change from spring to summer. Using a four-year surface radar precipitation data set, hourly images of instantaneous extreme rain rates were separated into isolated and mesoscale precipitation features from March through August for the four-year period of 2009–2012. Results show that that compared to isolated convection, mesoscale precipitation organization is more commonly associated with higher extremes in instantaneous rainfall in the southeastern U.S. Extreme rain values tied to mesoscale organization shift eastward and toward the coasts from spring to summer, while extreme rain from isolated convection is mainly a summer phenomenon concentrated in Florida and along the coastal plain. The implication is that dynamical processes favoring mesoscale organization such as high shear associated with baroclinic circulations are more associated with higher values of extreme rain, while thermodynamic forcing and local circulations favoring isolated convection are associated with lower values of extreme rain.